Conditions of formation of seed floras of the Holocene and paleoclimatic reconstructions of the Atlantic period in the territory of Belarus - Litviniuk, Georgy I.; Vorobey, Maksym V. (Journal of the Belarusian State University. Geography and Geology, 2026)
The results of paleocarpological study of Holocene deposits in the territory of Belarus are presented. The conditions of occurrence of Holocene deposits in the section «Brod» on the Western Berezina River, in the sections «Morino», «Karolin – Sverzhen’» and «Podbarany» on the Neman River, in the section «Semenovichi» on the Usa River, in the section «Peski» on the Zelvyanka River, in the section «Borovaya» on the Dnieper River are considered. The composition of fossil seed complexes and the conditions of their formation are analysed. The most thermophilic key species from the composition of woody, shrub and herbaceous plants are determined, based on which the temperature indicators of the warmest month (average temperature +18.8 °С for July) and coldest month (average temperature – 0.5 °С for January) for the Atlantic period of the Holocene are reconstructed using the climatic plant range method.
Keywords: paleogeography; paleoclimate; paleocarpological analysis; seed flora; Atlantic period; Holocene